P274 Seasonal variation in initiation and discontinuation of domiciliary non-invasive ventilation: a 12-month cohort study. (2nd December 2011) - Khatun, Y; Murphy, P B; Davidson, A C; Hart, N
Abstract : Introduction: Domiciliary non-invasive ventilation (NIV) is an established treatment for patients with chronic respiratory failure. Although the proportion of patients that discontinue NIV is reported from clinical trial data, observational cohort studies often lack these details. Furthermore, adherence to treatment and patient retention is enhanced in clinical trials as a consequence of well-defined patient selection and greater clinical and non-clinical support for trial patients. Aim: To investigate initiation, discontinuation and rationale for discontinuation in patients initiated on domiciliary NIV in a regional home mechanical ventilation centre over a 12-month period. Methods: All data were collected prospectively from a discharge summary database form 1 January to 31 December 2010. Monthly initiation and discontinuation trends and rationale for discontinuation were analysed across differing diagnostic groups. Results: 200 patients were initiated (123) and discontinued (77). Chronic obstructive pulmonary disease (COPD), neuromuscular and chest wall disease (NMD and CWD) and obesity related respiratory failure (ORRF) were the most frequent diagnoses for initiation (26.0%, 23.6%, 50.4%, respectively) and discontinuation (13.8%, 22.8%, 41.6%, respectively). Overall initiation rates were constant throughout the year with a fall in the number of COPD patients during the Summer. Death (52.6%) and poor adherence to the ventilator prescription (19.2%) were the commonest reasons for discontinuation across all groups. As expected, death was the commonest indication for discontinuation in the COPD and NMD and CWD group and poor adherence in the ORRF group (Abstract P274 table 1 ). Discussion: Although there is seasonal variation in the initiation of NIV in the COPD patients, this is not apparent in the NWD, CWD and ORRF patients. However, there is a seasonal variation in stopping NIV, which may relate to excess mortality in the Winter and Spring months. Further analysis of these trends is required to establish a cause and effect relationship for initiation and discontinuation of domiciliary NIV in clinical practice.